EKONOMI ISLAM DALAM PEMIKIRAN M. UMER CHAPRA DAN M. NEJATULLAH SIDDIQI - Rifqi Rivaldi (EL MUDHORIB : Jurnal Kajian Ekonomi dan Perbankan Syariah, 2021)
Islamic economics is the basis of Muslims in knowing the principles of sharia economic teachings based on the Qur'an and Hadith in the economic thought of M Nejatullah S and M Umer Chapra. The purpose of this study is to explain the economic thinking of M Nejatullah S and M Umer Chapra and their contribution to the country's economic system. This research is a type of historical research with library data sources. The results of this study indicate that the economic thinking of M Nejatullah Siddiqi related to sharia insurance or commonly called takaful is a new product that was born as a result of the rejection of conventional insurance which in its operations practices usury, maysir, and gharar. While Chapra's economic thinking is based on the concept of monotheism, caliphate, and justice, in its operations, Chapra divides this concept of caliphate into four main points, namely: universal brotherhood, resources as a mandate (resources are trusted), a simple lifestyle ( humble lifestyle), and human freedom.